Clonus: beats provoked by the application of a rhythmic force. - Walsh, E G (1976)
(1) Clonus has been elicited by using a printed motor in nine patients with sustained ankle clonus. (2) When a dorsiflexing biasing force was applied to the foot the amplitude, but not the frequency, of the clonus varied according to the strength of the force. (3) When the biasing force was withdrawn there could be, for some seconds, continuing EMG evidence of a rhythmic discharge. (4) The clonus did not synchronise with an externally applied rhythmic force. In all relevant observations beats were set up between the clonus and the applied force. (5) When clonus was started by the abrupt application of bias the waveform in successive trials was fairly closely repeatable. (6) Beats were also established in two cases of wrist clonus. (7) It is concluded that clonus is not due to the self re-excitation of proprioceptive reflexes but is dependent on a spinal generator, the rate of beating of which is normally independent of peripheral circumstances, although it may be switched on and its activity maintained by appropriate events.